Torta de algodão na dieta de cordeiros confinados - Lima, Leni Rodrigues (2012)
Two experiments were conducted in the area of Sheep Experimental Farm of Federal University of Mato Grosso, to evaluate intake, nutrient digestibility, ruminal characteristics, microbial protein synthesis, performance and economic feasibility of production of lambs in feedlot fed diets with increasing levels of cottonseed cake (CSC) (0, 7, 14, 21 and 28% of the diet on dry basis). The roughage: concentrate diet was 40:60, and the corn silage roughage used. In experiment I evaluate intake and digestibility of nutrients, as well as the characteristics: pH and ruminal amonical nitrogen (RAN), blood glucose and microbial efficiency, in which used five no specific breed sheep rumen, castrated, initial weight of 51.3 kg, in randomized 5 x 5 Latin square, with five periods with lasting 15 days each. The levels of CSC did not affect the intake of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), total carbohydrates (TC) and total digestible nutrients (TDN ), but there was an increase of 0.6907 kg / animal / day and a decrease of 0.0069 kg / day / animal for consumption of ether extract (EE) (P <0.10) and non-fiber carbohydrates (NFC) (P <0.05) respectively for each 1% ED added to the diet. The apparent digestibility of DM, OM, CP, EE, NDF and TDN increased linearly (P <0.05) depending on the levels of CSC, while for the NFC had no effect. Provision of increasing levels of CSC did not alter ruminal pH values, since for RAN concentrations of was linearly reduced (P <0.01) of 0.1143 mg / dL for each 1% addition of CSC in the diet. The second experiment was conducted to evaluate the performance, consumption and economic viability of lambs fed diets with increasing levels of cottonseed cake (0, 7, 14, 21 and 28% dry matter). Were used 40 lambs woolless, mahos uncastrated, with average initial age and weight of three and a half months and 14.6 kg, respectively, distributed in 20 pens with an area of 4.06 square meters each. The levels of CSC did not affect average daily gain, dry matter intake, feed conversion, carcass yield and loin eye area of the lambs, whose means were: 0.210 kg/animal/day, 0.875 kg/day, 4.13 kg, 39.53% and 7.20 cm2, respectively. The CSC may be included in the diet of feedlot lambs up to 28% of MS without causing negative effects on intake, digestibility of nutrients, microbial efficiency, animal performance and reduce production costs and improve gross margin.